A Clinical Decision Support System for Predicting Invasive Breast Cancer Recurrence: Preliminary Results - Massafra, Raffaella; Latorre, Agnese; Fanizzi, Annarita; Bellotti, Roberto; Didonna, Vittorio; Giotta, Francesco; La Forgia, Daniele; Nardone, Annalisa; Pastena, Maria; Ressa, Cosmo Maurizio; Rinaldi, Lucia; Russo, Anna Orsola Maria; et al. (Frontiers in Oncology, 2021)
The mortality associated to breast cancer is in many cases related to metastasization and recurrence. Personalized treatment strategies are critical for the outcomes improvement of BC patients and the Clinical Decision Support Systems can have an important role in medical practice. In this paper, we present the preliminary results of a prediction model of the Breast Cancer Recurrence (BCR) within five and ten years after diagnosis. The main breast cancer-related and treatment-related features of 256 patients referred to Istituto Tumori “Giovanni Paolo II” of Bari (Italy) were used to train machine learning algorithms at the-state-of-the-art. Firstly, we implemented several feature importance techniques and then we evaluated the prediction performances of BCR within 5 and 10 years after the first diagnosis by means different classifiers. By using a small number of features, the models reached highly performing results both with reference to the BCR within 5 years and within 10 years with an accuracy of 77.50% and 80.39% and a sensitivity of 92.31% and 95.83% respectively, in the hold-out sample test. Despite validation studies are needed on larger samples, our results are promising for the development of a reliable prognostic supporting tool for clinicians in the definition of personalized treatment plans.